Metal-based cathodes for hydrogen production by alkaline water electrolysis: Review of materials, degradation mechanism, and durability tests - Esfandiari, Naeemeh; Aliofkhazraei, Mahmood; Colli, Alejandro N.; Walsh, Frank C.; Cherevko, Serhiy; Kibler, Ludwig A.; Elnagar, Mohamed M.; Lund, Peter D.; Zhang, Dongke; Omanovic, Sasha; Lee, Jaeyoung (Progress in Materials Science, 2024)
The Department of Energy (DOE) has identified the reduction of H2 production costs as a prominent objective. Therefore, any factor that influences the system's functionality and subsequently production cost is deemed significant. The stability of the cathode is a crucial factor in ensuring high operational reliability; however, its treatment in the existing literature remains inadequate. This review aims to identify the key challenges associated with the stability of HER electrodes and provides a comprehensive understanding of various cathodic degradation mechanisms. In the present investigation, genuine circumstances encountered by cathodes in the industrial sector are considered. Special attention is devoted to Fe-based materials, which are deemed favorable and economical options, whereas the deterioration mechanism of Ni-based counterparts, such as cutting-edge materials, is scrutinized. Furthermore, the limitations of using the E-pH diagram, which is a commonly employed tool for predicting stable phases under specific conditions, are discussed. In addition, the cost implications of developing alkaline water electrolyzer (AWEL) stacks are considered. Finally, a comprehensive discussion is presented on the durability of cathode plates, including an analysis of the factors that impact their predicted lifetime and protocols that facilitate the acquisition of more realistic stability results.
CRIS-Team Scopus Importer:2024-05-17
Keywords: Alkaline Water Electrolysis; Bipolar Plates; Cathodic Degradation; Cost; Durability; Electrolyzer; Lifetime Estimation; Stability; Stainless Steel; Water Splitting